Maize relay intercropping with fodder crops for small-scale farmers in central Brazil. (17th August 2020) - Baldé, Alpha Bocar; Scopel, Eric; Affholder, François; Da Silva, Fernando Antonio Macena; Wery, Jacques; Corbeels, Marc
Abstract: Relay intercropping of maize with fodder crops is a promising option for sustainable intensification of dairy small-scale farms in the Cerrado of Brazil. Twenty-six intercropping trials were conducted on farmers' fields with the following experimental treatments: sole maize crop cropping (MS), maize- Brachiaria intercropping (MB) and maize-pigeon pea intercropping (MP). The trials were managed by the farmers, i.e. choice of conventional tillage (CT) versus no-tillage (NT), sowing dates, fertilization and weed control. Maize grain yield varied strongly across the farmer fields, from 100 to 5900 kg ha −1 in the MS treatment, 500 to 6900 kg ha −1 in MP and 300 to 5500 kg ha −1 in MB. Intercropping did not significantly affect maize grain yields under NT, but yields were reduced under CT in one out of two seasons. Maize yields in the intercropped systems were also higher under NT than CT. Total biomass productivity was significantly higher in the maize-fodder than in the sole maize system. An increased interval between sowing of maize and fodder crop significantly reduced the fodder crop biomass. Relay intercropping, especially in combination with NT, is a promising option if crop calendars and fertilization are properly managed by farmers to reduce interspecific competition between the maize and fodder crop.